NOTARY LEGALITY REGARDING THE VALIDITY OF AUTHORITY IN THE IMPLEMENTATION OF BANKRUPTCY AUCTIONS - Sannia Oktavienty (UNES Law Review, 2022)
The capacity of the notary in recording the minutes of auction is only limited to the implementation of the auction which is carried out on a non-voluntary basis. Minister of Finance Regulation Number 189/PMK.06/2017 concerning Class II Auction Officers position notaries as class II auction officials only having the authority to carry out voluntary non-execution auctions. This means that other types of auctions are not the work domain of class II auction officials. So that the capacity and capability of the notary cannot touch the bankruptcy auction process. Based on this, problems arise, namely regarding the legality of the position of a Notary in the implementation of a bankruptcy auction after the debtor is declared bankrupt and the legal validity of recording a bankruptcy auction that does not involve a Notary. Based on these problems, notaries actually have legal legality to carry out legal actions for bankruptcy auctions as stipulated in Article 185 paragraph (1) of the KPKPU Law that all objects must be sold in public in accordance with the procedures specified in the legislation. The procedure for traded assets in the management of bankruptcy assets is actually inseparable from the involvement of a notary in the bankruptcy auction process against a debtor who is declared bankrupt because the notary is the only public official who is given the authority to take legal actions to make an authentic deed regarding all acts and or an agreement according to the provisions of the applicable laws and regulations as stipulated in Article 15 paragraph (1) of the UUJN. Based on this, notaries need to have stronger authority to be able to be involved in execution auctions, especially those related to bankruptcy auctions. Strengthening the authority of a notary as a bankruptcy auction official is because a notary is a legal profession that is considered the most capable of forming an authentic deed of legal action on bankruptcy assets. Therefore, if the notary's authority is added to be able to be directly involved in the bankruptcy auction, it will greatly assist the process of completing the implementation of the bankruptcy estate.